2023
DOI: 10.1111/geb.13633
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of functional diversity along latitudinal gradients of species richness in eleven fish families

Abstract: Aim: As we enter an era of major biodiversity shifts, understanding large-scale biodiversity patterns has become crucial for ecological and conservation purposes. Often, conservation priorities are based on concepts derived largely from species richness, yet recent work shows that different facets of biodiversity are also crucial for proper ecosystem continuity, function and services. One facet of biodiversity increasingly relevant to conservation is functional diversity. Here, we aim to improve our understand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 77 publications
0
6
0
Order By: Relevance
“…Other studies on a latitudinal gradient in SR demonstrated differential latitudinal patterns between different taxonomic units (e.g. classes of helminths in Preisser 2019 or families of fish in Diamond and Roy 2023). In our case, this could not be the reason behind the substantial variation of SR along latitudes because this variation has been found even when the analyses were restricted to separate families (Supporting information for three flea families in the north‐eastern quadrant).…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…Other studies on a latitudinal gradient in SR demonstrated differential latitudinal patterns between different taxonomic units (e.g. classes of helminths in Preisser 2019 or families of fish in Diamond and Roy 2023). In our case, this could not be the reason behind the substantial variation of SR along latitudes because this variation has been found even when the analyses were restricted to separate families (Supporting information for three flea families in the north‐eastern quadrant).…”
Section: Discussionmentioning
confidence: 93%
“…As mentioned above, the latitudinal distributions of the SR, PD and FD of fleas and their hosts demonstrate different patterns. The lack of a strong correlation between SR and FD has been found in other taxa Ganade 2001, Diamond andRoy 2023). This suggests that either some species occurring at a latitude band are functionally redundant (Rosenfeld 2002) or that the functional traits selected for the calculation of FD were not informative enough (Llopis-Belinguer et al 2019).…”
Section: Functional Diversitymentioning
confidence: 97%
See 2 more Smart Citations
“…woodland salamanders), whereas the Cambrian explosion of metazoan life famously produced an early burst of morphological disparity and ecological function with relatively low taxonomic diversity [7]. Major taxonomic classes or orders established during the Cambrian might also be expected to exhibit rapid ecological expansion; however, most studies of these clades have quantified morphology as a proxy for ecological functional groups [2,3,8,9], potentially confounding these two biodiversity dimensions [10]. In fact, echinoderms showed an early burst in morphology but not in function [11].…”
Section: Introductionmentioning
confidence: 99%